Microgaps and Demineralization Progress around Composite Restorations. (August 2015) - Turkistani, A.; Nakashima, S.; Shimada, Y.; Tagami, J.; Sadr, A.
This study investigated the influence of adhesives and marginal sealing on demineralization progress using optical coherence tomography (OCT). Cavities (4 × 2 mm) were prepared in bovine incisors and restored using Clearfil SE Protect (SP), Bond Force (BF), Scotchbond Universal (SB), or G-Bond Plus (GB), followed by Estelite Flow Quick flowable composite. The control group received no adhesive ( n = 10). After 3-d incubation in artificial saliva and 10, 000 thermal cycles, gaps at enamel and dentin margins were measured at 8 locations on cross-sectional images obtained from each restoration using swept-source OCT at 1310-nm wavelength. Specimens were demineralized using acidified gel (pH = 4.5) for 5 wk and scanned every week to monitor the lesion progress at the same marginal locations. Repeated-measures analysis of variance showed that demineralization period and adhesive type and their interaction had a significant effect on the lesion size in both substrates ( P < 0.001). SP, BF, and SB had significantly lower enamel and dentin initial gaps than the control and GB ( P < 0.05). Enamel lesion progress was slower in the fluoride-releasing adhesives SP and BF and significantly different from SB, GB, and the control ( P < 0.001). SP and BF dentin lesions were significantly different from GB and the control ( P < 0.001), but not from SB ( P > 0.05). A significant positive correlation ( P < 0.05) was found between initial gap length and formed lesion size in both substrates, which was stronger in enamel ( r = 0.63) than dentin ( r = 0.35). Microgaps forming at the margins of restorations depend on adhesives and significantly contribute to the progress of demineralization around the margins, while fluoride release may decrease the rate of progression.